EVALUASI TINGKAT KEPATUHAN PENERAPAN INSTRUKSI PENGGUNAAN APD PADA KARYAWAN PANEN DI PERKEBUNAN KELAPA SAWIT - Jamiatun Nisa; Rusli Anwar; Yuanita (JURNAL AGRIMENT, 2022)
This research aims to evaluate the level of employee compliance in using PPE, know the work productivity of harvest employees, describe the characteristics of workers then know the level of understanding of employees in using PPE and know the rate of occurrence of work accidents and know the extent of providing PPE for employees. Data collection related to compliance with the implementation of apd use of harvest employees is obtained through observation methods, interviews and data from the company. To analyze this data, the analysis of the data used in this study is collected from research sources using descriptive and mathematical analysis methods that are then averaged and calculated percentages. Based on the results of the employee compliance rate in the highest use of PPE, namely 100% boots. The highest crop work productivity was in afd 1 with an average achievement of 105.6%. Characteristics of respondents that the age of the most workers is at the age of 20-30 years elementary education level and work experience 1-2 years. Respondents' understanding of PPE is a percentage of 92%. Cases of work accidents occurred in February and October in 2020 a total of 3 times. Fulfillment of APD with 30 needs available only 29